Agglomeration economies and geographic distribution of manufacturing industries in Turkey - Kent, Oya (My University, 2015)
A generally observed phenomenon is that most economic activities and industries are not uniformly distributed across space but tend to cluster in certain locations in developed and developing countries. Turkey, as a developing country, also exhibits uneven distribution of economic activity across regions, notably manufacturing employment demonstrates a prominent diversification between eastern and western regions. This study measures and evaluates the agglomeration patterns in Turkish manufacturing industries for the period 2003-2008 by exploring a confidential establishment level micro dataset compiled by TurkStat. In measuring agglomeration, it follows the methodology proposed by Ellison and Glaeser (1997) (EG) in which they present an agglomeration index of plants based on a test of comparison between the observed geographic distribution of plants and a random distribution. It also relates the geographic concentration measures to industry characteristics and agglomeration forces proposed by theory. The main finding is that Turkish manufacturing industries follow higher levels of agglomeration on average compared to developed countries. However, the stylized fact that low-technology and traditional industries exhibit higher levels of agglomeration is also valid for the case of Turkey. The study also aims to test factors behind agglomeration based on the hypotheses asserted by theory. Main finding related to that is, transportation costs do have a significant effect on industrial agglomeration, as suggested by New Economic Geography. The contribution of this study to the literature is twofold: (i) the period it analyses has not been examined within agglomeration framework before, so it will shed light on the agglomeration patterns of Turkish manufacturing for the post-2000 period and (ii) the EG index it employs is the first attempt to measure agglomeration in Turkish manufacturing using a micro level dataset.

Ekonomik aktivite ve endüstrilerin büyük bir kısmının mekan içinde eşit dağılmadığı, belirli bölgelerde kümelenme gösterdiği hem gelişmiş hem de gelişmekte olan ülkelerde genel olarak gözlemlenen bir olgudur. Türkiye, gelişmekte olan bir ülke olarak bölgeleri arasında ekonomik aktivitenin dağılımı anlamında eşitliksiz bir yapı sergilemektedir, özellikle imalat sanayi istihdamı doğu ve batı bölgeleri arasında göze çarpan bir farklılaşma mevcuttur. Bu çalışma, TÜİK tarafından sağlanan mikro verileri kullanarak 2003-2008 dönemi için Türk imalat sanayindeki yığılma örüntüsünü ölçerek değerlendirmeyi amaçlamaktadır. Yığılma ölçümünde Ellison and Glaeser (1997) (EG) tarafından önerilen, firmaların gözlemlenen dağılımı ile rassal dağılımı arasındaki karşılaştırmaya dayanarak elde edilen yığılma endeksini kullanmaktadır. Bunun yanında coğrafi yoğunlaşma ölçümlerini teori tarafından öne sürülen yığılma kuvvetleri ile ilişkilendirmektedir. Çalışmanın ana bulgusu, Türk imalat sanayinin gelişmiş ülkelere oranla ortalamanın üzerinde bir yığılma gösterdiğidir. Ayrıca, düşük teknolojili ve geleneksel endüstrilerin daha yüksek düzeyde yığılma gösterdiği olgusu Türkiye için de geçerli olmaktadır. Çalışma aynı zamanda, yığılmanın ardındaki faktörleri teorilerin öne sürdüğü hipotezlere dayanarak test etmeyi amaçlamaktadır. Bununla ilgili temel bulgu Yeni Ekonomik Coğrafya yaklaşımının belirttiği gibi taşımacılık maliyetlerinin endüstriyel yığılmalar üzerinde önemli bir etkisinin olduğudur. Bu çalışma iki yönden var olan literatüre katkıda bulunmaktadır. Birincisi, incelenen dönem yığılma çerçevesi içinde daha önceki çalışmalar tarafından analiz edilmemiştir, bu bağlamda çalışma Türkiye imalat sanayinin yığılma örüntüsüne 2000 sonrası dönem için ışık tutmaktadır. İkincil olarak da Türk imalat sanayindeki yığılmayı ölçmek için mikro veri kullanarak EG endeksini ilk kez hesaplama girişiminde bulunmaktadır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2015
Keywords: Agglomeration; Geographic concentration; Manufacturing; Yığılma; Coğrafi yoğunlaşma; İmalat